Exploring biodiversity & fisheries biology: a fundamental knowledge for sustainable fish production - Arshad, Aziz (Universiti Putra Malaysia Press, 2014)
Research on fisheries biology receives less attention due to several underlying factors. However, the opportunity is still great as the scope under fisheries biology is very wide and furthermore, our waters is rich in fish species that are of importance to the fisheries industry. Malaysia dependence on capture fisheries is still strong, as aquaculture production stays at around 30% of the total fish production. Research on wide range of marine organisms that help to enhance the fish production ought to be encouraged. In comparison to finfish, molluscan shells and crustaceans are lagging behind in term of their biological information and have long been receiving less interest from the researchers. This is despite seafood demands for shrimps, crabs and shells are consistently high and on the increase. Taking the matter as an important issue, our research team in UPM has for the past two decades focused and engaged on biological research of this group of fish resources. Knowledge and output on the biological aspects of these invertebrate species is important in many ways; primarily it might help to propel the development of new species for shellfish aquaculture whether as a culture species itself or alternatively acting as a source of live foods for hatchery use. Acting along this objective and tagging up with national interest on increasing fish production, works on the reproductive and feeding biology as well as diversity and ecology are undertaken. The lecture will take a closer look at the research being assumed by us and will discuss the results and findings on several invertebrate species that we studied.